Knowledge's theory in scientific research: a current scope - V. Ramírez, Augusto (2009)
Knowledge is a conscious, intentional and individual act to learn object's qualities and is firstly referred to who knows but also to the object thing what is known. Its development has been close to human thought evolution. Epistemology, the science that studies knowledge, is based in scientific research that begins with a hypothesis exposition and develops afterwards with mathematical models to have verifiable and valid conclusions. Scientific research is an accepted and validated process for new facts or questions solutions guided to recognize principles and laws that sustain man's life in the world. It owns methods based on hypothesisdeduction/ induction complemented with statistics and calculation probabilities. Scientific researchers should know its theory and evolution because they are indispensable tools in research and its good handling will allow technical and suitable answers for any hypothesis.